Consensus process to agree upon surgical quality assurance processes within a pragmatic, multicentre randomised clinical trial comparing targeted axillary dissection and axillary node clearance: the TADPOLE-TOGETHER project - Stuart A McIntosh; Kirsty Roberts; Lucy Culliford; Natalie S Blencowe; Kerry Avery; Jessica Harris; Shelley Potter; Sophie Rees; Yazan Masannat; Peter Barry; David Dodwell; Elsa Marques; et al. (BMJ Open)
Introduction Patients with node-positive breast cancer having primary surgery currently undergo axillary node clearance (ANC) to reduce the risk of breast cancer recurrence. Evidence that this highly morbid procedure improves survival is lacking, but approximately 30% of patients will develop lifelong complications which significantly impact their quality of life.Targeted axillary dissection (TAD) may be a safe, less morbid alternative to ANC and will be evaluated in the upcoming Targeted Axillary Dissection versus axillary node clearance in patients with POsitive axillary Lymph nodes in Early breast cancer (TADPOLE) randomised controlled trial.TAD is not currently routine practice in patients having primary surgery, so it is vital that the procedure is performed in an agreed upon, standardised way within the trial and procedure fidelity monitored to ensure the results are generalisable and will be accepted by the surgical community. Robust surgical quality assurance (SQA) is essential. Here we describe the first phase of the TADPOLE SQA, a consensus process with the breast surgical community to agree upon how (1) surgery should be performed and standardised; (2) procedure fidelity will be monitored and (3) requirements for surgeon credentialling within the trial.Methods and analysis The consensus process will have three phases:Generation of a long list of possible components of TAD from a scoping review and expert opinion. Identified items will be categorised and formatted into Delphi consensus questionnaire items.At least two rounds of an online Delphi survey in which at least 100 breast cancer surgeons will rate the importance of mandating/prohibiting, standardising and/or monitoring each component.A consensus meeting with surgeons to discuss, agree upon and ratify the approach to SQA within TADPOLE.Ethics and dissemination Ethical approval has been obtained from the University of Bristol Faculty of Health Sciences Ethics Committee. Educational materials including videos and webinars will be developed and shared with surgeons participating in TADPOLE. Results will be presented at national/international meetings and published in peer-reviewed journals.